2014
DOI: 10.1007/s10571-014-0050-0
|View full text |Cite
|
Sign up to set email alerts
|

microRNA Expression Pattern Modulates Temozolomide Response in GBM Tumors with Cancer Stem Cells

Abstract: Temozolomide (TMZ) is widely used to treat glioblastoma multiforme (GBM). Although the MGMT gene methylation status is postulated to correlate with TMZ response, some patients with a methylated MGMT gene still do not benefit from TMZ therapy. Cancer stem cells (CSCs) may be one of the causes of therapeutic resistance, but the molecular mechanism underlying this resistance is unclear. microRNA (miRNA) deregulation has been recognized as another chemoresistance modulating mechanism. Thus, we aimed to evaluate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 69 publications
1
34
0
Order By: Relevance
“… 8 , 103 , 104 , 105 , 106 , 107 Therefore, miRNAs can serve as potential targets for anti-GSC therapeutics. 103 , 108 , 109 , 110 …”
Section: Micrornas and Other Epigenetic Factors In Gbcsmentioning
confidence: 99%
“… 8 , 103 , 104 , 105 , 106 , 107 Therefore, miRNAs can serve as potential targets for anti-GSC therapeutics. 103 , 108 , 109 , 110 …”
Section: Micrornas and Other Epigenetic Factors In Gbcsmentioning
confidence: 99%
“…A multivariate analysis using paraffin-embedded (FFPE) ependymoma samples from patients has identified let-7d, miR-596, and miR-367 to be associated with increased overall survival [ 143 ]. These microRNAs are shown to regulate stem cells in other cancers like breast and brain [ 147 , 148 ]. Furthermore, miR-34a was shown to be overexpressed in supratentorial ependymomas which are associated with better prognosis in comparison to infratentorial tumours [ 143 ].…”
Section: Ependymomamentioning
confidence: 99%
“…MiRNAs abnormally express in a variety of tumors and may have the effects of proto-oncogene or anti-oncogene (Stahlhut Espinosa and Slack, 2006). Accumulating researches showed that regulating the expression of miRNAs could enhance the benefits of chemotherapeutics in the treatment of tumors (Tezcan et al, 2014). Overexpressed miR-31 enhances the antitumor activity of TMZ in human GBM cells (Zhou et al, 2015).…”
Section: Introductionmentioning
confidence: 99%